2013
DOI: 10.1016/s1514-0326(13)60015-x
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of the Nonlinear Relationship Between Environmental Regulation and Manufacturing Productivity

Abstract: for their excellent research support and to Flor Brown and Lilia Dominguez for giving us access to their own data. We also thank to three anonymous referees for their useful comments. All errors are our own responsibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 16 publications
0
11
1
Order By: Relevance
“…On the other hand, appropriate intervention can avoid deteriorating environmental quality results from enterprise excessive competition. The above results coincide with the nonlinear effect from the perspective of investment, which is significantly different from previous scholars' research (Sanchez-Vargas et al, 2013;Yin et al, 2015) [26,27]. The latter tells us the government should enhance research of the optimal intensity of invest-based environmental regulation in different areas.…”
Section: Conclusion and Policy Recommendationscontrasting
confidence: 60%
See 1 more Smart Citation
“…On the other hand, appropriate intervention can avoid deteriorating environmental quality results from enterprise excessive competition. The above results coincide with the nonlinear effect from the perspective of investment, which is significantly different from previous scholars' research (Sanchez-Vargas et al, 2013;Yin et al, 2015) [26,27]. The latter tells us the government should enhance research of the optimal intensity of invest-based environmental regulation in different areas.…”
Section: Conclusion and Policy Recommendationscontrasting
confidence: 60%
“…Other scholars believe that there is nonlinear transformation between environmental regulation and environmental pollution (Sanchez-Vargas et al, 2013; Yin et al, 2015; Chakraborty and Chatterjee, 2017; Xie et al, 2017) [26][27][28][29]. Sanchez-Vargas et al (2013) found that the nonlinear effects of manufacturing productivity and environmental regulation are reflected in the size of the enterprise [26]. Wang and Shen (2016) showed an inverted "U" relationship with three thresholds between China's environmental regulation and environmental productivity based on data envelopment analysis model [15].…”
Section: Literature Reviewmentioning
confidence: 99%
“…includes environmental practices containing PACE and ET. As in the literature (Rubashkina et al 2015;Sanchez-Vargas et al 2013;Yang et al 2012, among others), PACE is used as a proxy for stringent environmental regulations. Besides, ET is considered as the proxy for firm compliance.…”
Section: Environmental Regulation and Tfp Convergencementioning
confidence: 99%
“…Some researchers have used a large set of indicators to determine the strength of environmental regulation policies: Sanchez-Vargas et al [59] used "the sum of investment on machinery and equipment aimed at reducing pollution at the plant level" to describe it. Kheder and Zugravu [31] employed the Z-score method to calculate the standardized values of three indicators-international environmental agreements, INGOs' members per million of population, and GDP/unit of energy used-and used them to capture countries' environmental regulation stringency.…”
Section: Data Descriptionmentioning
confidence: 99%
“…In line with China's particular situation, we do not use the method by Kheder and Zugravu [31] because NGOs do not play a leading role in environmental regulation in China. We do not include the indicator used by Sanchez-Vargas et al [59] due to data availability.…”
Section: Data Descriptionmentioning
confidence: 99%